Перспективи впровадження відновлюваних джерел енергії в єдину енергетичну систему - Дудніков, С. М.; Галько, Сергій Віталійович; Halko, Serhii; Мірошник, О. О.; Савченко, О. А.; Зеленков, Денис Максимович; Zelenkov, Denys (Запоріжжя : Видавничий дім «Гельветика», 2025)
UA: У статті запропоновано використовувати біогазові установки (далі – БГУ) як високогнучкі джерела енергії. При ухваленні рішення про їх використання є прогнозування показників енергоефективності запропонованої системи енергопостачання на основі біогазу порівняно з поточною централізованою моделлю. Показники енергоефективності оцінювалися за допомогою аналізу енергетичних балансів, побудованих з використанням усереднених статистичних даних про втрати та споживання енергії на біогазових об’єктах. Цей підхід рекомендується використовувати на ранніх етапах визначення технічних вимог при побудові або модернізації наявних енергетичних систем. Упровадження БГУ є економічно конкурентоспроможним порівняно із централізованими системами, як-от теплові електростанції та котельні. Інтеграція БГУ допоможе зменшити національну залежність від імпортованої енергії, виправити дисбаланси в енергетичній системі та знизити вартість енергії – електричної, теплової чи хімічної (наприклад, добрив). /// EN: Against the backdrop of the rapid growth of renewable energy production – primarily from wind turbines and solar power plants – there is a growing need to balance their variable capacity to ensure stability of operation. A key characteristic of energy sources from wind farms and solar power plants is their dependence on weather conditions, which leads to unstable energy production. When large-scale renewable energy sources (RES) is integrated into power systems, there are problems with maintaining both static and dynamic stability of operating modes. If the share of RES in the total energy balance exceeds 2 %, existing grids often lack the technical ability to cope with generation and flow peaks, which requires infrastructure modernization and grid modernization. Research shows that the most effective one-size-fits-all approach to balancing this variability is to build flexibility into the energy system of other RES, which allows for adjustments in electricity production or consumption in response to fluctuations from wind farms and solar power plants. The article proposes to use biogas plants (BGP) as highly flexible energy sources. An important step in deciding whether to use them is to predict the energy efficiency of the proposed biogas-based energy supply system compared to the current centralized model. Energy efficiency indicators were evaluated using the analysis of energy balances constructed using averaged statistical data on energy losses and consumption at biogas facilities. The introduction of BGPs as local energy sources turns out to be economically competitive compared to centralized systems, such as thermal power plants (TPPs) and boiler houses. BGP have a similar structure to these systems, but work with less equipment required to operate. The integration of BGPs can help reduce national dependence on imported energy, correct imbalances in the energy system due to their flexibility, and reduce the cost of energy – electrical, thermal or chemical (e.g. fertilizers) – for specific manufacturing plants. Data on the energy balance show that 73 % of the energy resources of the BGP are concentrated in biomass.
Prospects for the introduction of renewable energy sources into the unified energy system
Keywords: біогазова установка; система енергопостачання; енергетичний баланс; сонячна електростанція; вітрова електростанція; енергоефективність; biogas plant; energy supply system; energy balance; solar power plant; wind farm; energy efficiency